Microscopic Phase-Field Simulation for the Influence of Interatomic Potential on the Precipitation Process of Ni75Al14MO11 Alloy - Ma, Qing-Shuang; Jin, Yu-Chun; Zhao, Yu-Hong; Sui, Huai-Ming; Zhang, Pu (Acta metallurgica sinica : English letters, 2016)
Abstract The process of γ＇ phase precipitating from Ni75Al14MO11 is studied by a computational simulation technique based on microscopic phase-field kinetics model. We studied the phase transformation with the purpose of clarifying the influence of the nearest interatomic potential V Ni-Al （the nearest interatomic potential） on the precipitation process of γ＇ phase. The result demonstrates that there are two kinds of ordered phases, respective Llo and L12 in the early stage, and Llo phase transforms into L12 phase subsequently. For L12 phase, Ni atoms mainly occupy α site （face center positions）, while Al and Mo atoms occupy fl sites （the vertex positions）. When VNi-Al is increased by 10 MeV, the occupation probability of Ni atoms on α sites and Al atoms on β sites are enhanced. Enhanced VNi-Al facilitates clustering and ordering of Al atom, which promotes the formation of the γ＇ phase. At last, the simulation result was discussed by employing the thermodynamic stability.